The Evaluation of AR Mobile App as a Learning Media for Children - Adhistya Erna Permanasari; Indriana Hidayah; Faizal M. Priyowibowo; M. Arifin Hidayat; Fachrul Budi Prayoga; Intan Sulistyaningrum Sakkinah (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
A user evaluation stage is an integral part of designing an application. A practical evaluation can provide an overview of the problems that arise in the application and improve the user experience. The Kupuku application is an augmented reality (AR)-based game application for learning about butterflies. The Kupuku application is specifically intended for children aged 6-13 years. The user sample was selected using a purposive sampling method with the criteria for users of elementary school-age children for the child user segment and their companions as the adult user segment. This study aims to evaluate the usability of the Kupuku game application to users. User evaluation was carried out to measure the application’s usability. The evaluation process was conducted on two user segments, namely 20 child users and 16 adult users. Assessment of children employed the Fun Toolkit and usability factor-based question - Nielsen method. The obtained results showed positive feedbacks. In contrast, the assessment for adult users utilized the system usability scale (SUS) and the user experience questionnaire (UEQ). The SUS score of 76 was included in the good category, and the UEQ score produced an excellent average. The test results indicate that this application can be accepted by users, both children, and adults.